2017
DOI: 10.1002/ajoc.201600570
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Transfer Reactions Triggered by Uncharged or Cationic Photosensitizer: Methodology for Generation of o‐Quinodimethane and Analysis of Back Electron‐Transfer Process

Abstract: Photoinduced electron transfer (PET) followed by back electron transfer (BET) reactions of 1,2-bis(a-styryl)benzenes 1,g enerates o-quinodimethane derivative 2 via the corresponding radical cation 2 · + .T his process serves as af acile methodt of orm o-quinodimethane intermediates. The intermediacy of 2 · + and 2 werec onfirmed by using various spectroscopicm ethods and trapping reactions with 3 O 2 and dienophiles. Kinetic analysisu sing nanosecond time-re-solved absorption showed that 2 · + was transformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In the present study, we targeted oxidative substrate activations from the uorescent singlet excited state of DCA ( 1* DCA), which has a very high oxidation potential of +1.99 V vs. SCE. 40 There have been many previous reports on photocatalytic applications of DCA [41][42][43][44][45][46][47][48][49] and related cyanoarenes, 40 though usually involving direct ultraviolet or blue excitation. Here, we targeted the formation of 1* DCA via upconversion of red light, to accomplish chemical transformations requiring high oxidative potentials, contrasting our recent studies, in which excitation of DCAc − led to thermodynamically challenging reductions under red irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we targeted oxidative substrate activations from the uorescent singlet excited state of DCA ( 1* DCA), which has a very high oxidation potential of +1.99 V vs. SCE. 40 There have been many previous reports on photocatalytic applications of DCA [41][42][43][44][45][46][47][48][49] and related cyanoarenes, 40 though usually involving direct ultraviolet or blue excitation. Here, we targeted the formation of 1* DCA via upconversion of red light, to accomplish chemical transformations requiring high oxidative potentials, contrasting our recent studies, in which excitation of DCAc − led to thermodynamically challenging reductions under red irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…TL in this case arises by decay of excited states in the form of fluorescence (FL) or phosphorescence (PH). A significant feature of this phenomenon is that it can readily provide insights into reactivities of radical ions, that play an important role not only in TL but also in photoredox reactions and organic electronic devices …”
Section: Methodsmentioning
confidence: 99%
“…TL in this case arises by decay of excited states in the form of fluorescence (FL) or phosphorescence (PH). A significant feature of this phenomenon is that it can readily provide insights into reactivities of radical ions, [3,4] that play an important role not only in TL but also in photoredox reactions [5,6] and organic electronic devices. [7][8][9] Previously, we reported that γ- [10,11] or X-ray [12] irradiation of methylcyclohexane (MCH) matrices (77 K) containing 2-aryl-1methylene-2-phenylcyclopropanes 1 (Scheme 1) followed by annealing leads to TL at around 130 K. For example, the 2,2diphenyl derivative 1 a displays vivid green TL.…”
Section: Rates Of Ring Opening Of Radical Cation Intermediates Governmentioning
confidence: 99%